Impact of magnetized non-linear radiative flow on 3D chemically reactive sutterby nanofluid capturing heat sink/source aspects. (January 2023) - Pasha, Amjad Ali; Hussain, Zubair; Alam, Md Mottahir; Kasim, Navin; Irshad, Kashif; Ali, Mehboob; Waqas, Muhammad; Khan, Waqar Azeem
Abstract: A recent advancement in fluid dynamics is the consideration of nanofluids which has an extraordinary thermal conductivity characteristics and upsurge heat transfer in fluids. This paper examines the heat and mass transfer properties of a steady 3D movement of a sutterby nanomaterial on a bidirectional stretching plane. Nanoparticle mass flow and convective boundary conditions are deliberated. In addition, the effect of heat generation/absorption and non-linear thermal radiation is explored. Moreover, the latest proposed model of the nanofluid has been pondered which involves controlling the nanoparticle volume element at the wall submissively relatively than dynamically. We introduced a similarity transformation to change the equations of boundary layer to a self-similar system after that processed analytically with the help of the bvp4c scheme. The outcomes of several control parameters on heat and mass transfer properties are shown among graphs then scrutinized. The systematic outputs of the Nusselt number are premeditated via tables. We observed that by increasing the estimates of the Lewis number ( L e ) indicates a reduction in the concentration field as well as the thickness of the equivalent boundary layer. Similarly, it is seen that the concentration field decreases rapidly according to the Brownian motion parameter as compared to the Lewis number ( L e ) .